Iron-based powder metallurgy materials, powder metallurgy processing methods and products

By using Mo, Co, Cr, Ni and other elements in iron-based powder metallurgical materials to form a high-entropy solid melt structure, and adding enhancers to the adhesive, the insufficient rotational performance of existing materials in the subdivided fields is solved. The problem is that high wear resistance, impact toughness and low energy consumption manufacturing of the parts are achieved.

CN116251950BActive Publication Date: 2024-12-17DONGGUAN YIHAO METAL MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111509172.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-10
Publication Date
2024-12-17
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

Existing iron-based powder metallurgical materials are difficult to meet the high requirements for rotational performance in specific application fields in sub-fields, and excessive hardness and extension properties of finished products lead to increased costs and manufacturing pressure, limiting the scope of application of materials in specific fields.

Method used

Four auxiliary elements, Mo, Co, Cr, and Ni, and trace Si and Cu, form a high entropy solid melt structure, combine with Fe matrix to control the content of C elements, form a compact metallographic structure, and add carbon to the adhesive. Reinforcing agents such as nanotubes, sulfide powders and low-density polyethylene improve rheology performance and adhesion and reduce viscosity.

Benefits of technology

It significantly improves the rotational performance, wear resistance and impact toughness of the material, improves the elongation in moderation, reduces production energy consumption and mold wear, and is suitable for the manufacturing of small precision components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116251950B_ABST
    Figure CN116251950B_ABST
Patent Text Reader

Abstract

The present invention provides an iron-based powder metallurgy material, including an iron-based powder and an adhesive, wherein the iron-based powder comprises, by mass percentage, 5-9% Mo, 6-9% Co, 7-9% Cr, 5-7% Ni, 0.2-0.8% Si, 0.1-0.2% Cu, ≤0.1% C, and the remainder is Fe and unavoidable impurities. The present invention also provides a powder metallurgy processing method, and during the molding process, the molding temperature is 170-175°C, the injection pressure is 90-95MPa, and the holding time is 15-20s. The present invention also provides a hinged part made of a powder metallurgy part using the above-mentioned powder metallurgy processing method. The powder metallurgy part provided in the present invention has excellent rotation performance, wear resistance, high strength, high elongation, and high impact toughness, and is particularly suitable for manufacturing and use as a hinged part and parts with other precision structural designs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of powder metallurgy raw materials and processing, and specifically relates to an iron-based powder metallurgy material, a powder metallurgy processing method using the powder metallurgy material, and a product prepared by the method. Background Art

[0002] Powder injection molding (PIM) is a new component processing technology that is formed by introducing plastic injection molding technology into the field of powder metallurgy. In traditional processing technology, parts with complex structures are usually physically split and prepared into individual parts, and then assembled into integral components. The use of PIM can simplify things and treat parts as integral components for manufacturing, which not only greatly reduces the production steps and simplifies the processing procedures, but also saves manufacturing costs and improves manufacturing efficiency. Mass-produced small, precise, three-dimensionally complex metal or ceramic parts with special performance requirements are particularly suitable for processing and manufacturing using powder injection molding technology.

[0003] Metal Injection Molding (MIM) is a near-net-shape forming process using metal powder as raw material. The process includes: uniformly mixing the metal raw material powder with a preset adhesive in a certain proportion to make a feed with rheological properties, injecting the feed into the mold cavity through an injection molding machine to make a part blank, then removing the adhesive from the blank, and finally sintering it at high temperature to obtain various metal parts with uniform microstructure and highly dense materials. Adhesives are generally mixtures of thermoplastics, wax-based materials or other materials. In the MIM process, the selection of metal raw material powder is particularly important. The composition of the appropriate metal powder mixture and the corresponding injection molding and sintering conditions must be determined, otherwise the component products will have weld lines, internal stress, cracks, bending deformation and other undesirable conditions.

[0004] Iron-based powder metallurgy materials are powder raw materials with iron powder as the main component. Iron-based materials have the characteristics of high melting point, high strength, high heat resistance, high compressive resistance, and low cost, so they are one of the most common optional materials in the MIM process. The most commonly used iron-based material in the MIM process is stainless steel powder material, which has been widely used in common fields such as smart phones, laptops, smart wearable devices, automobiles, home appliances, and medical devices. However, precisely because of its increasingly wide application, its application characteristics have also been gradually subdivided, and higher and higher requirements have been put forward for the material properties of powder sintering in various subdivided fields. In the prior art, the improvement direction of powder metallurgy stainless steel powder materials often emphasizes increasing the overall performance of the components after forming, and the demand for special structures in the subdivided fields has not been deeply explored, thereby limiting the further expansion of the scope of application of this type of powder material in specific application fields. Summary of the invention

[0005] Stainless steel is one of the most commonly selected metal materials in traditional application fields. Products in the automotive industry, consumer electronics, and medical equipment are also constantly upgraded. In particular, parts directly sintered from stainless steel powder are widely used. Taking the automotive industry as an example, the number of parts prepared by powder metallurgy on some models exceeds 15% of the total number of parts. In the prior art, the components of stainless steel powder metallurgy materials are often the same as the chemical composition of stainless steel grades (refer to "GB / T 20878-2007 Stainless Steel and Heat-resistant Steel Grades and Chemical Composition"), or slightly adjusted on this basis. Although stainless steel materials are familiar to the industrial field, there are still great differences between components prepared by powder metallurgy and stainless steel materials prepared by actual smelting and processing. Especially in the sub-sectors, iron-based powder metallurgy materials that are proportioned or slightly improved by the existing stainless steel material components cannot achieve the best application effect.

[0006] In the field of small component manufacturing, for devices such as automobile intelligent systems, small automobile accessories, smart phones, tablet computers, smart watches, etc., which are assembled from a variety of small components, simply improving the overall component performance is not only difficult to achieve, but also often "over-quality", which will cause greater pressure on costs and manufacturing processes, thereby losing competitiveness. For example, the key performance point of the rotating components in the above-mentioned devices lies in the improvement of rotation performance, without paying too much attention to the overall hardness, elongation and significant deformation performance (because the lower limits of the hardness, elongation and deformation performance of iron-based parts can often meet the requirements, and there is no need to consider too much during the development process), and at the same time, consider increasing wear resistance and impact toughness.

[0007] Due to the research on the subdivided field, the purpose of the present invention is to provide an iron-based powder metallurgy material suitable for components requiring strong rotation performance. The present invention not only provides a composition formula of the iron-based powder metallurgy material, but also provides a method for processing the above-mentioned iron-based powder metallurgy material, as well as a rotating component prepared by the above-mentioned processing method.

[0008] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:

[0009] In one aspect, the present invention provides an iron-based powder metallurgy material, comprising an iron-based powder and an adhesive, wherein the iron-based powder comprises the following components by mass percentage:

[0010]

[0011] The balance is Fe and unavoidable impurities;

[0012] The chemical composition of the blank after sintering the iron-based powder metallurgy material is as follows:

[0013] C 0.02~0.06%

[0014] N≤0.0007%

[0015] O 0.005~0.015%.

[0016] Commonly used stainless steel powder metallurgy materials in the prior art include martensitic chromium steel (2Cr13, 4Cr13, etc., i.e. common grades such as 304 and 316) based on chromium content, martensitic chromium-nickel aged stainless steel (with increased Ni content), and other alloying elements mainly added in one or two to three alloying elements.

[0017] Different from the prior art, the iron-based powder in the present invention adopts a component with a mass percentage of four auxiliary additive elements Mo, Co, Cr, and Ni that is closer, and does not rely on a single element to play a special role in the Fe alloy, but forms a solid solution alloy through a plurality of auxiliary elements and trace auxiliary elements, forming an overall dense, compact and wear-resistant organizational structure. The four auxiliary additive elements Mo, Co, Cr, and Ni form a high-entropy solid solution structure with trace added Si and Cu, so that the Fe matrix and other alloy organizations are closely combined. At the same time, by controlling the content of the C element (avoiding the introduction of too many C elements), the metallographic structure of the workpiece after sintering using the above-mentioned powder metallurgy material presents a change to pearlite, overcoming the instability caused by high entropy, making the overall metallographic structure more compact and the grain size finer, thereby greatly improving the rotation performance of the material, that is, improving the wear resistance and impact toughness of the workpiece, and the elongation is also appropriately improved. Although the hardness cannot be significantly improved, it has met the use in the above-mentioned field, thereby avoiding other design, cost, and manufacturing problems caused by the excess performance of the structural parts.

[0018] Using the iron-based powder of the iron-based powder metallurgy material in the present invention as a powder metallurgy raw material can also effectively control the contents of the three organic elements C, N, and O, greatly suppressing the defects such as material embrittlement, excessive porosity, and reduced surface finish of the workpiece caused by excessive organic element content.

[0019] More preferably, in the iron-based powder in the above iron-based powder metallurgy material, a component composition in which the mass percentage of Mo is 5.5-6.0% and the mass percentage of Co is 7.0-7.5% is adopted, so that a material composition with the best impact toughness can be obtained.

[0020] It is further preferred that, in the iron-based powder in the above-mentioned iron-based powder metallurgy material, the component composition has a mass percentage of Mo of 8.0-8.5%, a mass percentage of Co of 8.0-8.5%, and a mass percentage of Ni of 5.5-6.0%, which can obtain a material composition with optimal strength and elongation.

[0021] The iron-based powder provided in the present invention can be used with common MIM adhesives on the market. Furthermore, by adding a reinforcing agent to the commercially available adhesive to improve the rheological properties of the adhesive, the forming properties of the iron-based powder metallurgy material in the present invention are further enhanced, which is of great significance for process improvement. In the present invention, further, the adhesive also includes a reinforcing agent with a mass percentage of 3 to 8%, and the reinforcing agent includes the following components by mass percentage:

[0022]

[0023]

[0024] The balance is paraffin and inevitable impurities;

[0025] The carbon nanotubes (CNTs) have a purity of ≥99.5%, a diameter of 50-80 nm, and a length of 80-160 μm; the zinc sulfide, ferrous sulfide, and antimony sulfide are all powdered particle raw materials with an average particle size of 1-2 μm; the low-density polyethylene has a density of 0.92-0.95 g·cm -3 .

[0026] The above-mentioned reinforcing agent has good adhesion with iron-based powder at the molding temperature and has low viscosity. Carbon nanotubes (CNTs) have excellent mechanical, electrical and thermal properties. The appropriate addition can not only enhance the rotation performance and elongation of the workpiece, but also have a certain weight reduction effect. However, carbon nanotubes also have problems such as poor wettability with the matrix and easy aggregation. In the present invention, on the one hand, three different sulfide powders are used in combination with carbon nanotubes. The single sulfide powder has a single polarity and particle shape and particle size, and the addition effect is not as good as the composite addition of multiple sulfides; on the other hand, adding stearic acid that can act as a surfactant can significantly reduce the viscosity of the adhesive; on the other hand, low-density polyethylene is used as a thickener to adjust the viscosity, so that the overall distribution of the reinforcing agent is uniform, which also promotes the degreasing process in the subsequent processing process. While ensuring that the components in the reinforcing agent are uniformly distributed, the presence of three sulfide powders can further increase the friction resistance of the workpiece, so that the mechanical properties such as smoothness and toughness of the sintered workpiece during the rotation process are greatly improved. The composition of stearic acid, low-density polyethylene and paraffin can not only reduce the intermolecular forces, thereby reducing the viscosity of the adhesive and enhancing its flexibility, but also serve as a bridge between the iron-based metal powder and other components to improve the uniformity and mixing performance of the raw materials, and avoid the undesirable conditions of separation, stratification and detachment of the iron-based powder and the adhesive during processing.

[0027] Furthermore, the reinforcing agent also includes 0.6-1.2% by mass of a silane coupling agent to further improve the surface tension between different interfaces, further improve the mixing performance and rheological properties, and significantly reduce the deformation of the parts caused by the separation of the iron-based powder and the adhesive during the molding, degreasing and sintering processes.

[0028] Furthermore, in order to ensure uniform mixing of the enhancer, the preparation method of the enhancer is formulated as follows:

[0029] Add the chopped block paraffin into a mixer heated to 75-85°C, mix at a speed of 30-40r / min for 10-15 minutes, then raise the temperature of the mixer to 140-145°C, add low-density polyethylene after the temperature stabilizes, continue mixing for 0.5-1h while keeping the speed unchanged, then add stearic acid, zinc sulfide, ferrous sulfide, carbon nanotubes and silane coupling agent in sequence, keep the temperature and speed unchanged and continue mixing the above mixture for 0.5-1h, stop mixing, wait for the mixture to cool naturally to room temperature and then take it out to obtain the desired reinforcing agent.

[0030] On the other hand, the present invention provides a processing method using the above-mentioned iron-based powder metallurgy material, namely, low-temperature and low-pressure molding - during the molding process, the molding temperature is 170-175°C, the injection pressure is 90-95MPa, and the holding time is 15-20s. The "low temperature and low pressure" referred to in the present invention refers to the MIM process in the prior art. The molding temperature of the MIM process in the prior art is often higher than 180°C and the injection pressure is greater than 100MPa. In the present invention, due to the improvement of the metal powder components and adhesives, it can be applied to lower pressures and temperatures, which not only reduces the energy consumption in the production process, but also indirectly increases the service life of the MIM mold, which is of great significance for industrial applications.

[0031] The last aspect of the present invention provides a powder metallurgy part, which is made by the processing method of the present invention and has excellent rotation performance, wear resistance, high strength, high elongation, and high impact toughness. Therefore, the above-mentioned part is particularly suitable for use as a hinge.

[0032] Furthermore, the hinge comprises:

[0033] A first articulated arm and a second articulated arm connected to each other, wherein the length of the first articulated arm and the second articulated arm are within the range of 30 to 60 mm and the thickness is within the range of 1 to 5 mm;

[0034] The first hinged arm and the second hinged arm are both provided with hinged holes, and the diameter of the hinged holes is 0.4-1.0 mm;

[0035] The hinge hole and the adjacent hinge hole parts are provided with a convex structure or a concave structure.

[0036] In the prior art, similar micro-precision structures such as small size, small through-hole structure, small boss, small groove, etc. cannot be prepared by integrated molding process (in actual production, they cannot be demolded, difficult to mold, sticky, and flashing). The reason is that the rheological properties of the raw materials during the molding process cannot meet the requirements of micro-molding. Since the iron-based powder metallurgy material provided in the present invention has excellent fluidity, its molding performance during the processing is also excellent, and it is particularly suitable for preparing precision components, or for parts with precision structural design. For example, the above-mentioned hinge with a set small-sized hinged arm, the hinge is also designed with microstructures such as small-aperture through-hole structure, convex structure or concave structure, and the molding accuracy of the above-mentioned microstructure does not exceed 10μm.

[0037] Furthermore, the protrusion depth or depression depth of the protrusion structure or the depression structure is preferably less than or equal to 60% of the thickness of the hinged arm where the structure is located. If the depth of the molding structure exceeds this limit, it may easily cause defects such as inability to demold, difficulty in molding, sticking, and flashing in actual production.

[0038] The iron-based powder metallurgy material provided by the present invention greatly improves the rotation performance of the material, that is, improves the wear resistance and impact toughness of the parts, and the elongation is also improved appropriately. Although the hardness cannot be significantly improved, it has met the use in the above-mentioned fields, thereby avoiding other design, cost, and manufacturing problems caused by excess performance of structural parts. The powder metallurgy method provided by the present invention is suitable for lower pressures and temperatures, which not only reduces the energy consumption in the production process, but also indirectly improves the service life of the MIM mold, which is of great significance for industrial applications. The powder metallurgy parts provided in the present invention have excellent rotation performance, wear resistance, high strength, high elongation, and high impact toughness, and are particularly suitable for manufacturing and use as hinges and parts with other precision structural designs. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the three-dimensional structure of a powder metallurgy part in an embodiment of the present invention;

[0040] Figure 2 for Figure 1 Schematic diagram of the bottom structure of the intermediate part;

[0041] Figure Number:

[0042] 10. Powder metallurgy parts;

[0043] 101. first articulated arm; 102. second articulated arm;

[0044] 1011, first hinge hole; 1012, first boss; 1013, second boss; 1014, first side hole; 1021, second hinge hole; 1022, third hinge hole; 1023, third boss. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and technical effect of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is clearly and completely described. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. In conjunction with the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer; if the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0046] In the description of the present invention, the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0047] In the description of the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0048] It should be understood that the weight of the relevant components mentioned in the embodiments of the present invention can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present invention is proportionally enlarged or reduced, it is within the scope disclosed by the present invention. Specifically, the weight described in the embodiments of the present invention can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0049] In addition, unless the context clearly uses otherwise, the expression of the singular form of a word should be understood to include the plural form of the word. The term "includes" or "having" is intended to specify the existence of a feature, quantity, step, operation, element, part or combination thereof, but is not used to exclude the existence or possible addition of one or more other features, quantities, steps, operations, elements, parts or combinations thereof.

[0050] Example 1: Composition of iron-based powder

[0051] The composition of the iron-based powder provided in this embodiment is shown in the following table, where the values ​​are in percentage by mass, and the remainder is iron and unavoidable impurities:

[0052] Example No. Mo Co Cr Ni Si Cu C 1-1 5.0 9.0 7.5 6.5 0.45 0.20 0.0045 1-2 5.2 8.1 7.5 6.5 0.56 0.15 0.0067 1-3 5.5 7.2 7.6 6.3 0.55 0.20 0.0060 1-4 5.7 7.0 8.0 6.7 0.61 0.16 0.0047 1-5 5.8 7.5 7.7 6.6 0.49 0.15 0.0067 1-6 5.9 7.4 7.7 6.8 0.33 0.15 0.0210 1-7 6.0 7.4 8.2 6.5 0.45 0.16 0.0068 1-8 5.7 7.0 8.0 5.4 0.62 0.15 0.0078 1-9 5.8 7.5 7.7 5.7 0.62 0.15 0.0066 1-10 5.9 7.4 7.7 6.0 0.55 0.15 0.0067 1-11 6.0 7.4 8.2 5.5 0.53 0.18 0.0065 1-12 6.3 8.4 8.0 6.9 0.62 0.16 0.0045 1-13 6.5 7.7 8.5 7.0 0.43 0.17 0.0065 1-14 7.0 7.9 7 / 6 7.0 0.76 0.15 0.0180 1-15 7.3 8.2 8.0 5.9 0.80 0.16 0.0045 1-16 7.5 8.1 8.5 5.8 0.55 0.15 0.0064 1-17 7.6 8.9 8.0 5.4 0.55 0.17 0.0061 1-18 7.8 8.8 9.0 5.5 0.50 0.15 0.0071 1-19 8.0 8.0 7.0 6.0 0.56 0.16 0.0065 1-20 8.2 8.2 7.6 5.8 0.50 0.18 0.0180 1-21 8.4 8.4 7.6 5.8 0.55 0.15 0.0189 1-22 8.5 8.5 7.8 5.5 0.53 0.15 0.0185 1-23 8.0 8.0 7.0 6.8 0.45 0.14 0.0064 1-24 8.2 8.2 7.6 7.0 0.37 0.12 0.0098 1-25 8.4 8.4 7.6 6.4 0.50 0.12 0.0180 1-26 8.5 8.5 7.8 6.5 0.62 0.12 0.0180 1-27 8.7 9.0 8.6 5.2 0.55 0.15 0.0077 1-28 9.0 6.5 9.0 6.7 0.45 0.14 0.0067

[0053] Example 2: Preparation of Enhancer

[0054] The enhancer embodiment is prepared according to the following table, the values ​​are weight percentages, and the balance is paraffin and inevitable impurities:

[0055]

[0056] The raw materials used in the above examples are all commercially available products. Among them, the purity of carbon nanotubes (CNTs) is ≥99.5%, the diameter is 50-80nm, and the length is 80-160μm; zinc sulfide, ferrous sulfide, and antimony sulfide are all chemically pure powdered granular raw materials, and the average particle size is 1-2μm (screened D50=1.2μm); the density of low-density polyethylene is 0.93g·cm -3 The silane coupling agent is commercially available silane coupling agent KH550.

[0057] The processing of the enhancer is:

[0058] Add the chopped block paraffin into a mixer heated to 80°C, mix at a speed of 30-40r / min for 10 minutes, then increase the temperature of the mixer to 140°C, add low-density polyethylene after the temperature stabilizes, and continue mixing for 0.5h while keeping the speed unchanged, then add stearic acid, zinc sulfide, ferrous sulfide, carbon nanotubes and silane coupling agent in sequence, keep the temperature and speed unchanged and continue mixing the above mixture for 1h, stop mixing, and take out the mixture after it cools naturally to room temperature to obtain the desired reinforcing agent.

[0059] In the above-mentioned Example 2, the reinforcing agent prepared in Example 2-4 has the best fluidity and wettability, so the reinforcing agent 2-4 is selected as the reinforcing agent for subsequent examples.

[0060] Example 3: Processing and manufacturing of powder metallurgy parts

[0061] The reinforcing agent of Example 2-4 is added at a mass ratio of 5% to a commercially available powder metallurgy adhesive (commercially available wax-based adhesive, also known as "binder", only needs to be wax-based in the present invention, without limiting the brand. The adhesive used in the present invention is a domestic brand of wax-based binder for powder metallurgy. The overall addition ratio of the binder can be adjusted based on the guided addition amount of commercially available products, which will not be elaborated here).

[0062] The binder prepared above (the amount added is adjusted in the range of 0.5-1.5% by mass percentage) and the iron-based metal powder in Example 1 are fully mixed in a mixer to make the powder and binder components evenly distributed in the entire feed. The feed particles prepared above are molded in a molding machine. During the molding process, the molding temperature is 175° C., the injection pressure is 95 MPa, and the holding time is 16 s.

[0063] After degreasing and sintering, the finished blank is obtained, as shown in the attached Figure 1 , 2 Since the processes of feeding, granulation, injection molding, degreasing, and sintering are all common process steps in the MIM process, those skilled in the art can adjust the equipment (temperature, pressure, and processing time) according to the different processing amounts and dispersion states of the alloy powder and the adhesive, and can obtain the optimal addition amount data by conducting a limited number of experiments according to the actual processing conditions, so they are not described in detail in the present invention.

[0064] Example 4: Part Structure and Performance Analysis

[0065] As attached Figure 1 , 2 The powder metallurgy component 10 shown is an articulated structure, which includes: a first articulated arm 101 and a second articulated arm 102 connected to each other, the first articulated arm 101 is 30 mm long, the second articulated arm 102 is 60 mm long and 4 mm thick.

[0066] The first hinge arm 101 is provided with a first hinge hole 1011, a first boss 1012, a second boss 1013, and a first side hole 1014. The second hinge arm is provided with a second hinge hole 1021, a third hinge hole 1022, and a third boss 1023. The diameter of the hinge hole is 0.5 mm, and the height of the first boss 1012, the second boss 1013, and the third boss 1023 is 2 mm.

[0067] The prepared parts 1-1 to 1-28 were tested for the C, N, and O element contents. The testing instruments were an infrared carbon-sulfur tester and an oxygen-nitrogen tester, and the testing methods were all standard methods.

[0068] The test results are as follows:

[0069]

[0070] Among the above-mentioned parts, Examples 1-3 to 1-7, 1-19 to 1-22 have low organic element content and best mechanical properties (rotational performance and impact toughness are improved by about 20% compared with the products in the prior art). The hinges in the above-mentioned embodiments all have excellent rotational performance, wear resistance, high strength, high elongation, high impact toughness, and hardness reaches the hardness limit of ordinary steel, and are suitable for manufacturing and use as parts with precise structural design.

[0071] It can be seen from the above embodiments that the iron-based powder metallurgy material provided by the present invention greatly improves the rotation performance of the material, that is, improves the wear resistance and impact toughness of the parts, and the elongation is also improved appropriately. Although the hardness cannot be significantly improved, it has met the use in the above fields, thereby avoiding other design, cost and manufacturing problems caused by the excess performance of the structural parts. The powder metallurgy method provided by the present invention is suitable for lower pressures and temperatures, which not only reduces the energy consumption in the production process, but also indirectly improves the service life of the MIM mold, which is of great significance for industrial applications.

[0072] It should be clear that in the present invention and its embodiments, the supporting structure of the die-casting components in the present invention is described and illustrated by using "mechanism", "device", "structure", etc. In the actual application process, those skilled in the art can adopt corresponding mechanical structures, mechanical devices, combinations of mechanical structures or devices based on the existing technology, as long as they can meet the technical purposes mentioned in the present invention.

[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An iron-based powder metallurgy material, comprising an iron-based powder and an adhesive, characterized in that: The iron-based powder comprises the following components by mass percentage: Mo 5~9% Co 6~9% Cr 7~9% Ni 5~7% Si 0.2~0.8% Cu 0.1~0.2% C ≤0.1% The balance is Fe and unavoidable impurities; The chemical composition of the blank after sintering the iron-based powder metallurgy material is as follows: C 0.02~0.06% N ≤0.0007% O 0.005~0.015% The adhesive further comprises a reinforcing agent in an amount of 3 to 8% by mass, wherein the reinforcing agent comprises the following components by mass percentage: Carbon nanotubes (CNTs) 5~8% Zinc sulfide 6~10% Ferrous sulfide 8~12% Antimony sulfide 3~5% Stearic acid 15~18% Low density polyethylene 18~20% The balance is paraffin and inevitable impurities; The carbon nanotubes (CNTs) have a purity of ≥99.5%, a diameter of 50-80 nm, and a length of 80-160 μm; the zinc sulfide, ferrous sulfide, and antimony sulfide are all powdered particle raw materials with an average particle size of 1-2 μm; the low-density polyethylene has a density of 0.92-0.95 g·cm -3 .

2. The iron-based powder metallurgy material according to claim 1, characterized in that: In the iron-based powder, the mass percentage of Mo is 5.5-6.0%, and the mass percentage of Co is 7.0-7.5%.

3. The iron-based powder metallurgy material according to claim 1, characterized in that: In the iron-based powder, the mass percentage of Mo is 8.0-8.5%, the mass percentage of Co is 8.0-8.5%, and the mass percentage of Ni is 5.5-6.0%.

4. The iron-based powder metallurgy material according to claim 3, characterized in that: The reinforcing agent also includes 0.6-1.2% by mass of a silane coupling agent.

5. The iron-based powder metallurgy material according to claim 4, characterized in that: The preparation method of the enhancer is: Add the chopped block paraffin into a mixer heated to 75-85°C, mix at a speed of 30-40r / min for 10-15min, then raise the temperature of the mixer to 140-145°C, add low-density polyethylene after the temperature stabilizes, continue mixing for 0.5-1h while keeping the speed unchanged, then add stearic acid, zinc sulfide, ferrous sulfide, carbon nanotubes and silane coupling agent in sequence, keep the temperature and speed unchanged and continue mixing the above mixture for 0.5-1h, stop mixing, wait for the mixture to cool naturally to room temperature and then take it out to obtain the desired reinforcing agent.

6. A powder metallurgy processing method, characterized in that: The iron-based powder metallurgy material according to any one of claims 1 to 5 is used, and during the molding process, the molding temperature is 170-175° C., the injection pressure is 90-95 MPa, and the holding time is 15-20 s.

7. A powder metallurgy product, characterized in that: The manufactured part is a hinged part prepared by the powder metallurgy processing method according to claim 6.

8. The powder metallurgy product according to claim 7, characterized in that: The hinge comprises: A first articulated arm and a second articulated arm connected to each other, wherein the length of the first articulated arm and the second articulated arm are within the range of 30 to 60 mm and the thickness is within the range of 1 to 5 mm; The first hinged arm and the second hinged arm are both provided with hinged holes, and the diameter of the hinged holes is 0.4-1.0 mm; The hinge hole and the adjacent hinge hole parts are provided with a convex structure or a concave structure.

9. The powder metallurgy product according to claim 8, characterized in that: The protrusion depth or the depression depth of the protrusion structure or the depression structure is less than or equal to 60% of the thickness of the hinged arm where the structure is located.